EFFECTIVENESS OF LIFE SKILLS COUNSELING WITH BIBLIOTHERAPY INCREASE THE QUALITY OF LIFE - Dudi, Josef (LPPM UM Metro, 2017)
This study the effectiveness of life skills counseling with bibliotherapy technique to increase clients’ quality of life in Rumah Damping BNNP Central Borneo. This study uses Pre Experimental Design approach with one group pre-test and posts test design. Clients of Rumah Damping BNNP Central Borneo can increase the quality of life after following life skills counseling with bibliotherapy technique. Group counseling service with bibliotherapy technique can increase the quality of life BNNP Central Borneo with the increasing clients’ life after following the services than before follows skills counseling services with bibliotherapy technique.